1975
DOI: 10.1021/jf60199a044
|View full text |Cite
|
Sign up to set email alerts
|

Volatile medium chain fatty acids and mutton flavor

Abstract: Mutton fat, cooked with or without meat added, produced a host of steam volatile fatty acids in trace amounts. These have been identified by GC-MS as medium chain normal, branched, unsaturated, oxygenated, and aromatic acids belonging to 11 homologous series. Odor properties of these acids have been evaluated and results in-dicate that the branched chain and unsaturated acids having 8 to 10 carbon atoms contribute to the undesirable flavor of cooked mutton. The 4-methyl branched Cg and Cio acids in particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
5

Year Published

1975
1975
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(97 citation statements)
references
References 7 publications
1
91
0
5
Order By: Relevance
“…The pattern of volatile fatty acids obtained from hydrolysis of mutton fats resembles in general that produced on heating the fat, and GC-MS analysis has shown that essentially the same series of acids are produced under both conditions (Wong et al 1975b). Differences between samples are manifest generally in the relative proportions of the odd and branchedchain acids present.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…The pattern of volatile fatty acids obtained from hydrolysis of mutton fats resembles in general that produced on heating the fat, and GC-MS analysis has shown that essentially the same series of acids are produced under both conditions (Wong et al 1975b). Differences between samples are manifest generally in the relative proportions of the odd and branchedchain acids present.…”
Section: Resultsmentioning
confidence: 86%
“…This strongly implies that other factors were contributing to the muttoniness in these samples. We have earlier concluded, independently from combined chemical and nasal appraisal studies, that other factors contribute to muttoniness and are present in the non-acid fraction of cooked mutton fat volatiles (Wong et al 1975b). This fraction is the subject of current investigations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations